Taṭwīr Kitāb Al-Qirā’ah Al-Rasyīdah Al-Mujallad 3 Bi Al-Tamrīnāt (Dirāsah Al-Baḥts Wa Al-Taṭwir Bi Ma‘Had Al-Manār) - Nurul Azmi; Moch. Fajarul Falah; Hilmi Hilmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The researchers found some issues related to most students struggling to understand the text because of new vocabularies that are unfamiliar for them. Students need the translation of those vocabularies in Arabic and some exercises that could help them understand the text in the book. Based on those issues, the researcher wants to help students by developing the Qirā’ah Rasyīdah book using exercises that could help the students understand the text. This research aims to find the method of developing this book using the exercises, finding the effectiveness of the book's utilisation. This study employs a research and development approach. There were 22 samples from 10th-grade students. We collected data using a test, questionnaire, and interview, while the data analysis technique uses a t-test formula using the SPSS program. Moreover, the result from this experiment is that the development method of Qirā’ah Rasyīdah by using exercise based on expert judgment is valid. Also, the result of using Qirā’ah Rasyīdah as a material for exercise effectively increases student understanding. Furthermore, this is based on the result of the level of (Sig.) 0,00 < 0,05, and this shows that the hypothetical hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.